2008
DOI: 10.1111/j.1095-8312.2008.00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, functional and evolutionary aspects of tail autotomy and regeneration in the ‘living fossil’Sphenodon (Reptilia: Rhynchocephalia)

Abstract: Tail autotomy and regeneration are less known in Sphenodon ('Reptilia': Rhynchocephalia) than in Squamata. We examined museum specimens, Sphenodon guntheri (N = 8) and Sphenodon punctatus (N = 172), wild Sphenodon punctatus (N = 19) and Sphenodon sp. skeletons (N = 8). In S. punctatus, unlike in typical Squamata, sexes had similar relative (intact) tail lengths, and regeneration frequencies; tail and body growth was isometric. Tail breakage was usually intravertebral, usually followed by ablation of a variably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 56 publications
0
35
0
2
Order By: Relevance
“…Corresponding to the relationship between bite force and territoriality in lizards, bite force has been shown to predict reproductive success; the hardest biters enjoy reproductive success nearly four times greater than similarly sized males with the weakest bites (Lappin & Husak 2005;Husak et al 2009). As with lizards (e.g., Lappin & Husak 2005), confrontations between male Sphenodon can be intense and lead to injuries (Buller 1877;Gans et al 1984;Gillingham et al 1995;Seligmann et al 2008). Pathologies occasionally found on Sphenodon dentaries may be the result of healed wounds or infections from wounds incurred during aggressive territorial encounters (Fig.…”
Section: Bite Force and Intrasexual Competitionmentioning
confidence: 99%
“…Corresponding to the relationship between bite force and territoriality in lizards, bite force has been shown to predict reproductive success; the hardest biters enjoy reproductive success nearly four times greater than similarly sized males with the weakest bites (Lappin & Husak 2005;Husak et al 2009). As with lizards (e.g., Lappin & Husak 2005), confrontations between male Sphenodon can be intense and lead to injuries (Buller 1877;Gans et al 1984;Gillingham et al 1995;Seligmann et al 2008). Pathologies occasionally found on Sphenodon dentaries may be the result of healed wounds or infections from wounds incurred during aggressive territorial encounters (Fig.…”
Section: Bite Force and Intrasexual Competitionmentioning
confidence: 99%
“…Studies on specific tissues that are regenerated in the tail have shown that the new cartilaginous tube and the spinal cord are similar to those of lizards (Alibardi & Meyer‐Rochow, , , ; Alibardi, ). Also, the regenerating scales, although smaller than the original ones and with irregular outlines (Seligmann et al, ), follow a morphogenetic process that resembles that seen in lacertilians (Alibardi & Maderson, ).…”
Section: Introductionmentioning
confidence: 99%
“…This could be a consequence of extended exposure to potential predators and thus an increased cumulative likelihood of injury and non-zero probability of survival following injury (Schall and Pianka, 1980;White et al, 1982;Willis et al, 1982;Seligmann et al, 2008;see Gregory and Isaac, 2005 for an alternative explanation). In Rhinechis scalaris, a terrestrial colubrid, an ontogenetic shift has been reported in the frequency of tail breakage, with the incidence of tail loss increasing as a logistic function of snake size (Pleguezuelos et al, 2010) resulting from predatory selection for medium-sized R. scalaris by their main predators (see also Gil and Pleguezuelos, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Tail breakage in snakes has been described as an effective antipredator strategy (Kaufman and Gibbons, 1975;Greene, 1988;Savage and Slowinsky, 1996;Aubret et al, 2005). Given that in snakes tail breakage is without regeneration and the conspicuous nature of this injury, comparisons between individuals, populations, and species are easy (Akani et al, 2002;Seligmann et al, 2008;Pleguezuelos et al, 2010). However, the interpretation of this injury is controversial (Willis Seligmann et al, 1996;Placyk and Burghardt, 2005), and it has been proposed that tail breakage may simply be evidence of inefficient predation (Schoener, 1979;Willis et al, 1982;Medel et al, 1988;Mushinsky and Miller, 1993) instead of predation risk (Jacksić and Busack, 1984).…”
Section: Introductionmentioning
confidence: 99%